Re-Framing Ghana-Korea People to People Solidarity - Khoo-Dzisi, A. (African and Asian Studies, 2019)
Movements of people between Africa and Asia have exponentially increased beyond diplomatic exchanges and development aid under neo-liberal globalisation. Similarly, Ghana-Korea encounters have expanded to people-to-people engagement, including sports and entertainment in recent years. This chapter explores new forms of people-to-people exchanges that go beyond ‘Ghana as the football nation’ and ‘Korea as the Samsung Republic’. The focus is to explore innovative ways of bridging cultures and transcending boundaries. This paper relies on primary data (participation observation, interviews) and secondary data (published academic, government and ephemeral material) to highlight new areas of collaboration, ranging from commerce and investment, academic exchanges, collaboration in art and cultural endeavours, and the merging of these areas in a mutually beneficial way. Korea can learn from Ghana’s cultural diversity and tolerance; Ghana can benefit from Korea’s success in turning its art and cultural industries into an important export. In considering new forms of Ghanaian-Korean cooperation that transcends the traditional paradigm, starting from the grassroots, critical perspectives and approaches are examined for building a sustainable partnership based on mutual respect and understanding.